Bertha Maxwell-Roddey : a modern-day race woman and the power of black leadership - Ramsey, Sonya Yvette (University Press of Florida, 2022)
"This biography of educational activist and Black studies pioneer Bertha Maxwell-Roddey examines a life of remarkable achievements and leadership in the early years of the desegregated South. Sonya Ramsey describes how Maxwell-Roddey and her peers turned hard-won civil rights and feminist milestones into tangible accomplishments in North Carolina and nationwide from the late 1960s to the 1990s"--